Involvement of the kynurenine pathway in the pathogenesis of Parkinson's disease. (August 2017) - Lim, Chai K.; Fernández-Gomez, Francisco J.; Braidy, Nady; Estrada, Cristina; Costa, Cristina; Costa, Silvia; Bessede, Alban; Fernandez-Villalba, Emiliano; Zinger, Anna; Herrero, Maria Trinidad; Guillemin, Gilles J.
Highlights: The kynurenine pathway is one of the major regulators of the immune response and is also implicated in the inflammatory and neurotoxic events in Parkinsonism. Kynurenic acid produced by astrocytes confers neuroprotection whereas quinolinic acid, released by activated microglia, can lead to excitotoxicity and amplify the inflammatory response. Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder characterized by loss of dopaminergic neurons and localized neuroinflammation occurring in the midbrain several years before the actual onset of symptoms. Neuroinflammation leads to microglia activation and release of a large number of proinflammatory mediators. The kynurenine pathway (KP) of tryptophan catabolism is one of the major regulators of the immune response and is also likely to be implicated in the inflammatory and neurotoxic events in Parkinsonism. Several neuroactive compounds are produced through the KP that can be either a neurotoxic, neuroprotective or immunomodulator. Among these metabolites kynurenic acid (KYNA), produced by astrocytes, is considered as neuroprotective whereas quinolinic acid (QUIN), released by activated microglia, can activate the N-methyl-d -aspartate (NMDA) receptor-signalling pathway, leading to excitotoxicity and amplify the inflammatory response. Previous studies have shown that NMDA antagonists can ease symptoms and exert a neuroprotective effect in PD both in vivo and in vitro . There are to date several lines of evidence linking some of the KP intermediates and the neuropathogenesis of PD. Moreover, it is likely that some of the KP metabolites could be used as prognostic biomarkers and that pharmacological modulators of the KP enzymes could represent a new therapeutic strategy for PD.